2006
DOI: 10.1209/epl/i2006-10021-1
|View full text |Cite
|
Sign up to set email alerts
|

Comment on “The Casimir effect for the Bose-gas in slabs” by P. A. Martin and V. A. Zagrebnov. Relation between the thermodynamic Casimir effect in Bose-gas slabs and critical Casimir forces

Abstract: Abstract. -In a recent letter, Martin and Zagrebnov [Europhys. Lett., 73 (2006) 1] discussed the thermodynamic Casimir effect for the ideal Bose gas confined in a thin film. We point out that their findings can be expressed in terms of previous general results for the Casimir effect induced by confined critical fluctuations. This highlights the links between the Casimir effect in the contexts of critical phenomena and Bose-Einstein condensation.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
31
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 4 publications
9
31
0
Order By: Relevance
“…The authors of [18] furthermore showed that these functions agree with those previously determined for a free Gaussian theory with an n-component real-valued order parameter φ [19] for the choice n = 2.…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…The authors of [18] furthermore showed that these functions agree with those previously determined for a free Gaussian theory with an n-component real-valued order parameter φ [19] for the choice n = 2.…”
Section: Introductionsupporting
confidence: 77%
“…This was pointed out and verified in [18]. We have explicitly shown that the same holds true for ABCs, DNBCs, and RBCs.…”
supporting
confidence: 73%
“…We now compare the above result with the analogous properties of the decay length κ imp of the thermodynamic Casimir force derived by us in [32]. The thermodynamic Casimir force can be presented with the help of the scaling function Υ(z) [10,32]…”
Section: Imperfect Bose Gasmentioning
confidence: 60%
“…It is a pure quantum effect because there is no force between the plates in classical electrodynamics. The Casimir effect for massive quantum particles is less explored than its counterpart for the photon gas [2], but the Casimir effect in a confined Bose-Einstein condensate (BEC) system caused by the quantum fluctuations of the ground state at zero temperature or thermal fluctuations at finite temperature has recently attracted considerable interest [2][3][4][5][6][7][8][9][10][11][12][13][14][15]. The Casimir effect caused by thermal fluctuations in a Bose gas confined by two slabs was studied under the Dirichlet, Neumann, and periodic boundary conditions by Martin and Zagrebnov [2].…”
mentioning
confidence: 99%
“…between the two slabs are no longer long-ranged; therefore, the confining boundaries are subject to a vanishing Casimir force [3].…”
mentioning
confidence: 99%